Composite material with core-shell structure as well as preparation method and application of composite material
By preparing core-shell structure composite materials, the lack of hydrophobicity and adsorption properties of solid adsorbents in the presence of water is solved, and efficient CO2 capture is achieved, which is suitable for purification of carbon dioxide-containing flue gas.
Patent Information
- Application Number
- CN202411566489.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-08-15
- Estimated Expiration
- 2044-11-05
AI Technical Summary
In the presence of water, existing solid adsorbents are difficult to maintain the hydrophobicity and CO2 adsorption capacity of the molecular sieve, and powder-state materials need to be used after molding, resulting in a reduced adsorption performance.
Core-shell structure composite materials are prepared by polymerizing specific monomers in the presence of initiators and dispersants to form spherical macroporous resins, and growing molecular sieves in situ inside them, and using template agents to regulate the hydrophilicity and pore structure of the molecular sieve.
It achieves strong hydrophobicity and high CO2 adsorption properties under high humidity conditions, high CO2/N2 selectivity, and the material can be used directly without molding, which is suitable for purification of carbon dioxide-containing flue gas.
Smart Images

Figure CN120479387A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon dioxide capture, and in particular to a core-shell structure composite material, a preparation method and applications thereof. Background Art
[0002] CO2 emissions are one of the main causes of climate change. Under the current energy structure, carbon capture, utilization and storage (CCUS) technology has become an indispensable component of carbon neutrality. Among the many carbon capture technologies, organic amine solution absorption has high separation efficiency, a wide range of applications, and high purity of CO2 product gas. However, it has always been plagued by problems such as short absorbent life, severe equipment corrosion, high energy consumption, and high costs. Compared with the former, solid adsorption technology uses porous solid materials as carriers and does not involve solvents. This can avoid the additional energy consumption caused by solvent evaporation and will not cause equipment corrosion. This technology has great potential for energy saving and consumption reduction and has good application prospects.
[0003] For solid adsorption technology, the adsorbent, as one of the core technologies, directly affects CO2 capture efficiency and cost. Numerous researchers at home and abroad have conducted research on adsorbents, but none have yet achieved the desired combination of high CO2 adsorption capacity, high selectivity, rapid kinetics, long life, low cost, and favorable geometric structures. Consequently, the advantages of solid adsorption technology cannot be fully realized.
[0004] Molecular sieves are one of many adsorption materials. Their structure features regularly ordered pores, a large specific surface area, and an adjustable structure, making them widely used in fields such as gas separation and catalysis. For molecular sieves that adsorb carbon dioxide, since flue gas after combustion often contains varying degrees of moisture, the molecular sieve preferentially adsorbs water molecules. During this process, the moisture occupies the molecular sieve's pores or CO2 adsorption sites, reducing the material's adsorption capacity and even directly leading to a loss of CO2 adsorption capacity. Therefore, maintaining the molecular sieve's inherently excellent carbon capture capabilities in the presence of water is a significant challenge.
[0005] 《Dynamic hydrophobic hindrance effect of zeolite@zeolitic imidazolate framework composites for CO2 capture in the presence of water》(J.Mater.Chem.A,2015,3,8091) discloses a method of combining pre-seeding and two-step temperature-controlled crystallization, introducing ZIF-8 material on the surface of 5A molecular sieve, and preparing a series of 5A@ZIF-8 composite materials with enhanced surface hydrophobicity. The composite material can reach 80.7% of the original 5A molecular sieve CO2 adsorption capacity in the presence of water. The method needs to first synthesize 5A molecular sieve, and then perform ZIF-8 two-step crystallization on its surface. The amount of ZIF-8 needs to be accurately controlled, which requires great difficulty. More importantly, although the hydrophobicity of the composite material prepared by the method after hydrophobic modification is improved, the CO2 adsorption capacity of the original molecular sieve cannot be maintained, resulting in a reduced adsorption effect.
[0006] CN115608326A discloses an adsorbent for flue gas under high humidity conditions, comprising an adsorbent core and a core-shell hydrophobic material coated on the adsorbent core and composed of an organic polymer. The preparation method comprises: (1) adding at least two molecular sieves of different configurations to a nitrate solution for ion exchange to obtain a mixed metal cation modified molecular sieve; (2) dissolving phenyltriethoxysilane in a dimethylformamide solution, then adding the mixed metal cation modified molecular sieve, and performing ultrasonic treatment to obtain a homogeneous mixture A; (3) adding styrene to the dimethylformamide solution, then adding divinylbenzene and stirring to obtain a homogeneous mixture B; (4) stirring and mixing the homogeneous mixture B with the homogeneous mixture A to obtain a mixture C; (5) adding azobisisobutyronitrile to the mixture C and stirring to obtain the adsorbent. This scheme adopts a post-modification method, which is prone to uneven modification and poor hydrophobic effect. In addition, the use of high molecular weight polymers can easily cause clogging of the molecular sieve pores, resulting in reduced adsorption capacity.
[0007] In addition, the adsorption material prepared by the above method after hydrophobic modification is still in powder form and cannot be used directly. It needs to be formed before use. Existing forming methods, such as extrusion, tablet pressing, pellets, rolling balls, etc., add binders without CO2 adsorption effect, and the dense structure formed after forming will increase the diffusion resistance, which will cause the CO2 adsorption performance of the material to be further reduced.
[0008] Therefore, there is an urgent need to develop a new method for hydrophobic modification of molecular sieve adsorbents, which can maintain the CO2 adsorption performance of the material while achieving the hydrophobicity of the molecular sieve and make the molecular sieve have a good geometric structure. This is of great significance for promoting the application of solid adsorption technology in the field of CO2 capture, especially for the efficient capture of CO2 under humid conditions. Summary of the Invention
[0009] In view of the problem that existing solid CO2 adsorbents are difficult to achieve both strong hydrophobicity and excellent CO2 adsorption performance, the present invention provides a core-shell structure composite material and its preparation method and application.
[0010] In order to achieve the above objectives, the present invention provides a first aspect of a method for preparing a core-shell structure composite material, comprising:
[0011] (1) in the presence of an initiator and a dispersant, a reaction system containing a monomer, a porogen, and water is subjected to a first reaction to obtain a spherical macroporous resin;
[0012] (2) subjecting the spherical macroporous resin to a second reaction with a first organic amine to obtain a modified resin;
[0013] (3) subjecting the modified resin to a third reaction with a solution containing an alkali, a template, a silicon source, and an aluminum source to obtain a core-shell structure composite material;
[0014] Wherein, the monomer is selected from at least one of an acrylate monomer, an alkenylbenzene and a silane coupling agent containing an unsaturated bond;
[0015] The template is prepared by a fourth reaction of raw materials containing a second organic amine and a modifier; wherein the modifier is selected from at least one of chloroalkanes, epoxy-containing acrylates, epoxy-containing alkanes, epoxy-containing alcohols, epoxy-containing ketones, and epoxy-containing silane coupling agents.
[0016] The second aspect of the present invention provides a core-shell structure composite material prepared by the preparation method described in the first aspect.
[0017] The third aspect of the present invention provides the use of the core-shell structure composite material described in the second aspect as a carbon dioxide adsorbent in the purification of flue gas containing carbon dioxide.
[0018] The preparation method of the core-shell structure composite material provided by the present invention is as follows: first, a specific monomer is polymerized under the action of a porogen to obtain a strongly hydrophobic polymer macroporous resin, and then a specific template is used to grow a molecular sieve in situ inside the polymer macroporous resin, and the surface hydrophilicity of the molecular sieve itself is modulated and the pore structure of the molecular sieve is optimized to prepare a composite material with a core-shell structure. Under the synergistic effect of the hydrophobic outer shell and the molecular sieve inside the shell, the core-shell composite material is given an excellent hydrophobicity, strong CO2 adsorption performance, and high CO2 / N2 selectivity. The composite material has a water absorption capacity of ≤22% by weight at 40°C and a relative humidity of 20% RH, a CO2 working adsorption capacity of ≥0.7 mmol / g at 40°C and 10% CO2 flue gas adsorption conditions and 120°C and 100% CO2 regeneration conditions, and a CO2 / N2 adsorption selectivity of ≥200 at 40°C and 10% CO2 and 70% N2. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following detailed description, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings:
[0020] Figure 1 This is a scanning electron microscope image (internal morphology) of the core-shell structure composite material prepared in Example 1 of the present invention.
[0021] Figure 2 This is a scanning electron microscope image (appearance and morphology) of the core-shell structure composite material prepared in Example 1 of the present invention.
[0022] Figure 3 This is the XRD diffraction pattern of the core-shell structure composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0023] The endpoints of the ranges and any values disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range and individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered to be specifically disclosed herein.
[0024] A first aspect of the present invention provides a method for preparing a core-shell structure composite material, the preparation method comprising:
[0025] (1) in the presence of an initiator and a dispersant, a reaction system containing a monomer, a porogen, and water is subjected to a first reaction to obtain a spherical macroporous resin;
[0026] (2) subjecting the spherical macroporous resin to a second reaction with a first organic amine to obtain a modified resin;
[0027] (3) subjecting the modified resin to a third reaction with a solution containing an alkali, a template, a silicon source, and an aluminum source to obtain a core-shell structure composite material;
[0028] Wherein, the monomer is selected from at least one of an acrylic ester monomer, an alkenylbenzene and a silane coupling agent containing an unsaturated bond;
[0029] The template is prepared by a fourth reaction of raw materials containing a second organic amine and a modifier; wherein the modifier is selected from at least one of chloroalkanes, epoxy-containing acrylates, epoxy-containing alkanes, epoxy-containing alcohols, epoxy-containing ketones, and epoxy-containing silane coupling agents.
[0030] According to the present invention, in the method for preparing the core-shell structure composite material, in step (1), a specific type of monomer is polymerized in the presence of a porogen to obtain a spherical macroporous resin. The spherical macroporous resin has a large particle size, a macroporous structure, and strong hydrophobicity.
[0031] According to the present invention, preferably, the average particle size of the spherical macroporous resin is 500-1000 μm.
[0032] According to the present invention, the pore size distribution range of the spherical macroporous resin is 3-6 μm.
[0033] According to the present invention, in the method for preparing the core-shell structure composite material, in step (1), preferably, the monomer can be selected from acrylate monomers and / or silane coupling agents containing unsaturated bonds, which can make the spherical macroporous resin obtained by polymerization have better hydrophobic properties.
[0034] According to the present invention, preferably, the acrylic acid ester monomer can be selected from at least one of isodecyl methacrylate, phenyl methacrylate, glycidyl methacrylate, isopropyl methacrylate, ethyl methacrylate, cyclohexyl methacrylate, dodecafluoroheptanoate methacrylate and pentafluorophenyl methacrylate.
[0035] More preferably, the acrylic acid ester monomer may be further selected from at least one of ethyl methacrylate, phenyl methacrylate, glycidyl methacrylate, dodecafluoroheptanoate methacrylate and pentafluorophenyl methacrylate.
[0036] According to the present invention, preferably, the alkenylbenzene may be at least one selected from styrene, 3-chlorostyrene and α-methylstyrene.
[0037] More preferably, the alkenylbenzene is styrene.
[0038] According to the present invention, preferably, the unsaturated bond-containing silane coupling agent may be selected from at least one of γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane and γ-(methacryloxy)propyltriethoxysilane.
[0039] More preferably, the silane coupling agent containing an unsaturated bond is γ-methacryloxypropyltrimethoxysilane.
[0040] According to a most preferred embodiment of the present invention, the monomers are glycidyl methacrylate, dodecafluoroheptanoate methacrylate, and γ-methacryloxypropyltrimethoxysilane. Preferably, the weight ratio of glycidyl methacrylate, dodecafluoroheptanoate methacrylate, and γ-methacryloxypropyltrimethoxysilane is 1:(0.9-1.2):(0.8-1.1).
[0041] According to the present invention, in the method for preparing the core-shell structure composite material, in step (1), the porogen can facilitate the construction of a macroporous structure of the material, providing space for the growth of the molecular sieve within the macropores of the resin in the subsequent step. Preferably, the porogen can be selected from at least one of toluene, xylene, and cyclohexane.
[0042] More preferably, the porogen is toluene.
[0043] According to the present invention, in the method for preparing the core-shell structure composite material, in step (1), the initiator is more broadly limited, for example, an azo initiator, a peroxide initiator, etc. can be used.
[0044] In the present invention, preferably, the azo initiator may include but is not limited to at least one of dimethyl azobisisobutyrate (AIBME), azodicarbonamide (ADC), azobisisopropylimidazoline hydrochloride (AIB1), azobiscyclohexylcarbonitrile (ACCN), azobiscyanovaleric acid (ACVA), azobisisopropylimidazoline (AIP), azobisisobutyronitrile (AIBN), azobisisovaleronitrile (AMBN) and azobisisoheptanenitrile (ABVN), and further azobisisobutyronitrile.
[0045] In the present invention, preferably, the peroxide initiator may include but is not limited to at least one of hydrogen peroxide, ammonium persulfate, sodium persulfate, potassium persulfate and benzoyl peroxide, more preferably benzoyl peroxide.
[0046] According to the present invention, in the method for preparing the core-shell structure composite material, in step (1), the dispersant can reduce agglomeration between particles and improve the stability of the reaction system. Preferably, the dispersant can be selected from at least one of polyvinyl alcohol, sodium carboxymethyl cellulose, and Tween.
[0047] More preferably, the dispersant is polyvinyl alcohol.
[0048] According to the present invention, in the method for preparing the core-shell structure composite material, in step (1), water can promote the formation of interconnected pores between the macropores, thereby increasing the porosity of the resin formed by polymerization.
[0049] According to the present invention, in the method for preparing the core-shell structure composite material, in step (1), preferably, the feeding amounts of the monomer, initiator, dispersant and water satisfy the following relationship:
[0050] The weight ratio of the monomer:initiator:dispersant:water is 1:(0.005-0.2):(0.5-1):(110-118).
[0051] According to the present invention, in the method for preparing the core-shell structure composite material, in step (1), preferably, the feeding amount of the porogen satisfies: the weight ratio of the monomer to the porogen is 1:(0.8-2).
[0052] According to the present invention, in the method for preparing the core-shell structure composite material, in step (1), the reaction system further includes a cross-linking agent, a surfactant and an optional reducing agent.
[0053] The crosslinking agent acts as a bridge between monomer molecules, crosslinking the polymer through chemical bonds to form a three-dimensional network structure, thereby improving the material's heat resistance, water resistance, and mechanical strength. Preferably, the crosslinking agent is selected from trimethylolpropane triacrylate and / or divinylbenzene. Preferably, the weight ratio of monomer to crosslinking agent is 1:(0.5-2).
[0054] The surfactant can reduce surface tension and promote the formation of a stable monomer emulsion reaction system. Preferably, the surfactant is selected from at least one of Span 80, a polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, sodium dodecylbenzene sulfonate, and polyvinyl alcohol. Preferably, the weight ratio of monomer to surfactant is 1:(0.2-0.5).
[0055] If the initiator is a peroxide, the reaction system also includes a reducing agent, which can react with the oxidant (initiator) to generate free radicals, accelerating the polymerization process. Preferably, the reducing agent is selected from at least one of N,N-dimethylaniline, N,N,N,N-tetramethylethylenediamine, and sodium sulfite. Preferably, the weight ratio of monomer to reducing agent is 1:(0.25-0.8).
[0056] According to the present invention, in the preparation method of the core-shell structure composite material, in step (1), the first reaction is a polymerization reaction, and its reaction conditions include: reacting under stirring and protective atmosphere; the reaction temperature is 50-90°C, preferably 60-80°C; the reaction time is 0.1-24h, preferably 0.25-24h; and the stirring rate is 150-350 rpm.
[0057] According to the present invention, the protective atmosphere can be selected from conventional options in the field of organic synthesis, such as nitrogen atmosphere, helium atmosphere, neon atmosphere, argon atmosphere, etc.
[0058] According to the present invention, in the first reaction, the size of the polymerized product is controlled by controlling the polymerization reaction at the above stirring rate, thereby controlling the size of the composite material finally prepared.
[0059] According to a preferred embodiment of the present invention, the spherical macroporous resin can be prepared by implementing step (1) in the following manner:
[0060] According to the above-mentioned feeding ratio, the monomer, cross-linking agent, surfactant, initiator, porogen and reducing agent are first mixed to obtain a mixed solution-I; then, the mixed solution-I is secondly mixed with water to obtain a mixed solution-II; then, under continuous stirring and a protective atmosphere, the mixed solution-II is poured into the dispersant aqueous solution to carry out the first reaction; after the reaction, the polymer product particles are separated and then dried to obtain a spherical macroporous resin.
[0061] In the above preferred embodiment, in order to obtain a better mixing effect of the oil and water phases, the second mixing is carried out under high-speed stirring conditions, preferably at a stirring rate of 3000-8000 rpm and a stirring time of 5-15 minutes.
[0062] In the above preferred embodiment, the concentration of the dispersant in the aqueous solution is preferably 0.0007-0.02 g / mL, which is more conducive to forming a spherical resin with a uniform particle size distribution after the reaction. The total weight of the solute water in the aqueous dispersant solution and the water added in the second mixing step is recorded as the amount of water added in the above step (1).
[0063] According to the present invention, in the method for preparing the core-shell structure composite material, in step (2), the spherical macroporous resin is functionalized with amino groups using the first organic amine through the second reaction, so that the precursor solution of the molecular sieve in the subsequent step can more easily enter the interior of the resin.
[0064] According to the present invention, the first organic amine can be selected from at least one of ethanolamine, triethanolamine, ethylenediamine, trimethylamine, isobutanolamine, polyethyleneimine, piperazine, N-(aminoethyl)piperazine, 2-aminomethylpiperidine, 1-(2-aminoethyl)piperidine and 2-amino-2-methyl-1-propanol.
[0065] According to the present invention, in the method for preparing the core-shell structure composite material, in step (2), preferably, the weight ratio of the spherical macroporous resin to the first organic amine is 1:(10-90).
[0066] According to the present invention, in the method for preparing the core-shell structure composite material, in step (2), the second reaction is carried out by impregnation. Preferably, the conditions of the second reaction include: a reaction temperature of 50-80°C and a reaction time of 0.5-3h.
[0067] According to a preferred embodiment of the present invention, step (2) can be implemented as follows to carry out the second reaction:
[0068] According to the above-mentioned feeding ratio, the spherical macroporous resin is immersed in the methanol solution of the first organic amine to carry out a second reaction, and then dried to obtain a modified resin.
[0069] Preferably, in the methanol solution of the first organic amine, the weight ratio of the first organic amine to methanol is 1:(1-5).
[0070] According to the present invention, in the preparation method of the core-shell structure composite material, in step (3), under the action of a specific template, the alkali, silicon source, and aluminum source undergo a third reaction in the spherical macroporous resin, and in situ crystallization and growth form a molecular sieve, and the template can adjust the hydrophilicity and pore structure of the molecular sieve, so that the synthesized molecular sieve itself has good hydrophobicity and excellent adsorption performance.
[0071] The template used in the present invention can be prepared by subjecting a raw material containing a second organic amine and a modifier to a fourth reaction. Preferably, in the fourth reaction, the second organic amine and the modifier are fed in such amounts that the weight ratio of the second organic amine to the modifier is 1:(0.5-3).
[0072] According to the present invention, the second organic amine can be selected from at least one of ethanolamine, triethanolamine, ethylenediamine, trimethylamine, isobutanolamine, polyethyleneimine, piperazine, N-(aminoethyl)piperazine, 2-aminomethylpiperidine, 1-(2-aminoethyl)piperidine and 2-amino-2-methyl-1-propanol.
[0073] Preferably, the second organic amine is selected from at least one of ethanolamine, ethylenediamine and polyethyleneimine, which is more conducive to regulating the molecular sieve structure and forming an enhanced hydrophobic effect.
[0074] According to the present invention, the modifier can be selected from at least one of ethylene glycol diglycidyl ether, epichlorohydrin, glycidol, 1,2-epoxycyclopentane, 2,3-epoxy-1-cyclohexanone, 3-[(2,3)-epoxypropyloxy]propylmethyldimethoxysilane and γ-glycidyloxypropyltrimethoxysilane.
[0075] According to the present invention, preferably, the conditions of the fourth reaction include: reaction temperature of 10-60° C., and reaction time of 12-48 h.
[0076] According to a preferred embodiment of the present invention, step (3) can be implemented as follows to carry out the fourth reaction:
[0077] The second organic amine, modifier, and solvent are thoroughly mixed according to the aforementioned feed ratio to produce a mixed solution III. The mixed solution III is then subjected to a fourth reaction, and the reaction product is dried to remove the solvent, thereby preparing a template. The solvent is preferably at least one of toluene, methanol, and N,N-dimethylformamide. Preferably, the weight ratio of solvent: (second organic amine + modifier + solvent) is (70-140):100.
[0078] According to the present invention, in the method for preparing the core-shell structure composite material, in step (3), the base can be selected from at least one of sodium hydroxide, potassium hydroxide and calcium hydroxide, preferably sodium hydroxide.
[0079] According to the present invention, in the method for preparing the core-shell structure composite material, in step (3), the silicon source and the aluminum source are broadly defined, and conventional silicon sources and aluminum sources in the field of molecular sieve preparation can be selected. Preferably, the silicon source can be selected from at least one of silica sol, water glass, sodium silicate, and sodium aluminum silicate. Preferably, the aluminum source can be selected from sodium metaaluminate and / or aluminum sulfate.
[0080] According to the present invention, in the method for preparing the core-shell structure composite material, in step (3), preferably, the feeding amounts of the modified resin, base, template, silicon source and aluminum source satisfy the following relationship:
[0081] The weight ratio of the modified resin: base: template: silicon source: aluminum source is 100: (195-1560): (390-1660): (1360-6162): (315-1560), preferably 100: (750-1560): (990-1660): (4660-6162): (810-1420).
[0082] According to the present invention, in the method for preparing the core-shell structure composite material, in step (3), the silicon source and the aluminum source are fed in the form of an aqueous solution containing both the silicon source and the aluminum source. Preferably, the total concentration of the silicon source and the aluminum source in the aqueous solution containing the silicon source and the aluminum source is 16-43% by weight.
[0083] According to the present invention, in the method for preparing the core-shell structure composite material, in step (3), the third reaction is carried out by impregnation. Preferably, the conditions of the third reaction include: a reaction temperature of 60-120°C and a reaction time of 6-24 hours.
[0084] According to a preferred embodiment of the present invention, step (3) can be implemented as follows to carry out the third reaction:
[0085] According to the above-mentioned feeding ratio, the base, template and aqueous solution containing silicon source and aluminum source are mixed to obtain mixed solution-IV, and the modified resin is immersed in the mixed solution-IV to carry out the third reaction. After the reaction is completed, the obtained granular product is dried to obtain a spherical core-shell structure composite material.
[0086] In the present invention, the molecular sieve synthesis is performed by impregnating the modified resin in a solution containing both a silicon source and an aluminum source, resulting in a core-shell composite material having excellent CO2 adsorption performance, hydrophobicity, and high CO2 / N2 adsorption selectivity. However, using a step-by-step impregnation method (i.e., the modified resin is first impregnated in a solution containing a single silicon source, then in a solution containing a single aluminum source; or the modified resin is first impregnated in a solution containing a single aluminum source, then in a solution containing a single silicon source) results in composite materials with inferior CO2 adsorption performance, hydrophobicity, and CO2 / N2 adsorption selectivity to the core-shell composite material produced by the method of the present invention.
[0087] The preparation method of existing core-shell structure adsorption materials is usually to first synthesize molecular sieves and then coat the surface of the molecular sieve with hydrophobic materials. The structure of the molecular sieve is not regulated. After the hydrophobic modification of the molecular sieve, it is difficult to maintain the original good CO2 adsorption performance, and the adsorption effect is reduced. Moreover, the adsorption material obtained after the hydrophobic modification is still a powder and needs to be formed before it can be used. The forming process will further cause the material's CO2 adsorption performance to lose. Compared with the existing technology, the present invention provides a new method for the directional synthesis of hydrophobic molecular sieves, which utilizes specific monomers to polymerize to form a strongly hydrophobic spherical macroporous resin, introduces a specific template to synthesize molecular sieves in the spherical macroporous resin, and achieves the adjustment of the surface hydrophilicity of the molecular sieve itself and the optimization of the molecular sieve pore structure. Through in-situ structural molding, a composite material with a core-shell structure is prepared. The average particle size of the composite material is 500-1000μm, which can be directly used for adsorption operations without the need for secondary molding. The core-shell structured composite material prepared by this method has a strong hydrophobic barrier effect, and the water absorption capacity at 40°C and a relative humidity of 20% RH is ≤22% by weight. The material has strong CO2 adsorption performance and high CO2 / N2 adsorption selectivity. Specifically, the CO2 working adsorption capacity at 40°C and 10% CO2 flue gas adsorption conditions and 120°C and 100% CO2 regeneration conditions is ≥0.7mmol / g, and the CO2 / N2 adsorption selectivity at 40°C and 10% CO2 and 70% N2 is ≥200.
[0088] The second aspect of the present invention provides a core-shell structure composite material prepared by the preparation method described in the first aspect.
[0089] According to the present invention, the core-shell structure composite material comprises: a resin shell and a molecular sieve core wrapped in the resin shell. Preferably, the weight ratio of the resin shell to the molecular sieve core is 100:(300-800).
[0090] According to the present invention, the core-shell structure composite material has a strong hydrophobic barrier effect. Preferably, the water absorption of the core-shell structure composite material at 25° C. and a relative humidity of 20% RH is ≤17% by weight.
[0091] According to the present invention, the core-shell composite material has strong CO2 adsorption performance. Preferably, the material has a CO2 working adsorption capacity of ≥ 0.7 mmol / g under flue gas adsorption conditions of 10% by volume CO2 at 40°C and regeneration conditions of 100% by volume CO2 at 120°C.
[0092] According to the present invention, the core-shell structure composite material has a high CO2 / N2 adsorption selectivity during the adsorption process. Preferably, the CO2 / N2 adsorption selectivity of the material is ≥200 at 40°C and 10% by volume CO2 and 70% by volume N2.
[0093] According to the present invention, the core-shell structure composite material has an average particle size of 500-1000 μm and can be directly used for CO2 adsorption without the need for secondary molding of traditional powdered molecular sieve materials.
[0094] The third aspect of the present invention provides the use of the core-shell structure composite material described in the second aspect as a carbon dioxide adsorbent in the purification of flue gas containing carbon dioxide.
[0095] The core-shell structure composite material provided by the present invention can be used as a solid adsorbent to purify flue gas containing carbon dioxide, especially has significant advantages in efficiently capturing CO2 under humid conditions, and has the comprehensive effects of good hydrophobicity, strong CO2 adsorption capacity, and high CO2 / N2 adsorption selectivity.
[0096] In the present invention, for CO2 capture under wet conditions, the purification target can include, but is not limited to, conventional air, kiln flue gas, coal-fired flue gas, natural gas purification, refinery tail gas, and other gases containing water vapor and carbon dioxide. Preferably, the water content of the carbon dioxide-containing flue gas is 10-50% by volume.
[0097] The present invention will be described in detail below through examples. In the following examples and comparative examples, unless otherwise specified, all methods are conventional; and all reagents and materials used, unless otherwise specified, can be obtained from commercial sources.
[0098] Example 1
[0099] (1) Monomers (dodecafluoroheptanoate methacrylate, γ-methacryloyloxypropyltrimethoxysilane and glycidyl methacrylate, weight ratio of 1:1:1), trimethylolpropane triacrylate (crosslinker), Span 80 (surfactant), benzoyl peroxide (initiator), toluene (porogen) and N,N-dimethylaniline (reducing agent) were mixed to obtain a mixture-I; the mixture-I was then mixed with water (stirred at 6000 rpm for 10 min) to obtain a mixture-II; the mixture-II was then slowly poured into a polyvinyl alcohol aqueous solution (polyvinyl alcohol concentration of 0.01 g / mL) under continuous stirring (250 rpm) and nitrogen protection to carry out polymerization reaction at 70°C for 0.5 h; after the reaction, the polymer product particles were separated and dried at 80°C for 6 h to obtain a spherical macroporous resin (denoted as B1, wherein the pore size distribution range is 3-4 μm);
[0100] The weight ratio of monomer: initiator: dispersant: water (including water in polyvinyl alcohol aqueous solution) is 1:0.015:1:110; the weight ratio of monomer: porogen is 1:1.45; the weight ratio of monomer: cross-linking agent is 1:1; the weight ratio of monomer: surfactant is 1:0.3; the weight ratio of monomer: reducing agent is 1:0.25;
[0101] (2) The spherical macroporous resin B1 was immersed in a methanol solution of polyethyleneimine (the weight ratio of polyethyleneimine to methanol was 1:2.3), reacted at 60°C for 1 h, and then dried at 80°C for 6 h to obtain a modified resin;
[0102] The weight ratio of spherical macroporous resin B1 to polyethyleneimine is 1:30;
[0103] (3) Preparation of template: Polyethyleneimine, γ-glycidyloxypropyltrimethoxysilane (modifier) and toluene were fully mixed to obtain a mixture-III. The mixture-III was reacted at 60°C for 24 hours. The reaction product was dried in a vacuum drying oven at 60°C for 24 hours to obtain a liquid template;
[0104] The weight ratio of polyethyleneimine to γ-glycidyloxypropyltrimethoxysilane is 1:1.6; the weight ratio of methanol to (polyethyleneimine+γ-glycidyloxypropyltrimethoxysilane+methanol) is 70:100;
[0105] Sodium hydroxide, the template, and an aqueous solution containing sodium silicate (without crystal water) and sodium metaaluminate (the total concentration of sodium silicate and sodium metaaluminate is 36% by weight) are mixed to obtain a mixed solution-IV; the modified resin is immersed in the mixed solution-IV and reacted at 90° C. for 6 hours. After the reaction is completed, spherical particle products are separated and dried at 120° C. for 12 hours to obtain a spherical core-shell structure composite material (denoted as P1, with an average particle size of 900 μm and a weight ratio of resin shell to molecular sieve core (NaX molecular sieve) in P1 of 100:700);
[0106] The weight ratio of modified resin: sodium hydroxide: template: sodium silicate: sodium aluminate is 100:780:1560:6120:830.
[0107] The internal morphology of P1 was tested by scanning electron microscopy. Figure 1 As shown, it can be seen that molecular sieves grow in the resin shell of P1; the apparent morphology is as follows Figure 2 As shown, the synthesized composite material is a regular nearly millimeter-scale sphere.
[0108] The XRD test results of P1 are as follows: Figure 3As shown, the original molecular sieve (NaX molecular sieve) corresponds one-to-one with the crystal planes
[111] ,
[331] and
[642] of the composite material, showing the characteristic peaks of the FAU topological structure, indicating that the molecular sieve was successfully synthesized in situ inside the resin.
[0109] Example 2
[0110] (1) Monomers of glycidyl methacrylate, dodecafluoroheptanoate methacrylate, and phenyl methacrylate (weight ratio of 1:1:1), trimethylolpropane triacrylate (crosslinker), Span 80 (surfactant), azobisisobutyronitrile (initiator), and toluene (porogen) were mixed to obtain a mixture-I; the mixture-I was then mixed with water (stirred at 6000 rpm for 10 min) to obtain a mixture-II; the mixture-II was then slowly poured into a polyvinyl alcohol aqueous solution (polyvinyl alcohol concentration of 0.01 g / mL) under continuous stirring (300 rpm) and nitrogen protection to carry out polymerization reaction at 70°C for 24 h; after the reaction, the polymer product particles were separated and dried at 80°C for 6 h to obtain a spherical macroporous resin (denoted as B2, wherein the pore size distribution range is 3-5 μm);
[0111] The weight ratio of monomer: initiator: dispersant: water (including water in polyvinyl alcohol aqueous solution) is 1:0.07:1:110; the weight ratio of monomer: porogen is 1:0.8; the weight ratio of monomer: cross-linking agent is 1:0.5; the weight ratio of monomer: surfactant is 1:0.2;
[0112] (2) The spherical macroporous resin B2 was immersed in a methanol solution of ethanolamine (the weight ratio of ethanolamine to methanol was 1:1.5), reacted at 70°C for 0.5 h, and then dried at 80°C for 6 h to obtain a modified resin;
[0113] The weight ratio of spherical macroporous resin B2 to ethanolamine is 1:50;
[0114] (3) Preparation of template: Ethanolamine, epichlorohydrin (modifier) and methanol were thoroughly mixed to obtain a mixture-III. The mixture-III was reacted at 25°C for 12 h. The reaction product was dried in a vacuum drying oven at 60°C for 24 h to obtain a liquid template;
[0115] The weight ratio of ethanolamine to epichlorohydrin is 1:0.7; the weight ratio of methanol to (ethanolamine + epichlorohydrin + methanol) is 80:100;
[0116] Sodium hydroxide, the template, and an aqueous solution containing sodium silicate nonahydrate and sodium metaaluminate (the total concentration of sodium silicate nonahydrate and sodium aluminum metaaluminate is 32% by weight) are mixed to obtain a mixed solution-IV; the modified resin is immersed in the mixed solution-IV and reacted at 100° C. for 6 hours. After the reaction, spherical particle products are separated and dried at 120° C. for 24 hours to obtain a spherical core-shell structure composite material (denoted as P2, with an average particle size of 800 μm and a weight ratio of resin shell to molecular sieve core (NaX molecular sieve) of 100:620 in P2);
[0117] The weight ratio of modified resin: sodium hydroxide: template: sodium silicate nonahydrate: sodium metaaluminate is 100:1170:1560:4740:1420.
[0118] Example 3
[0119] (1) Monomers (ethyl methacrylate, glycidyl methacrylate and pentafluorophenyl methacrylate, weight ratio of 1:1:1), trimethylolpropane triacrylate (crosslinker), Span 80 (surfactant), benzoyl peroxide (initiator), toluene (porogen) and N,N-dimethylaniline (reducing agent) were mixed to obtain a mixture-I; the mixture-I was then mixed with water (stirred at 6000 rpm for 10 min) to obtain a mixture-II; the mixture-II was then slowly poured into a polyvinyl alcohol aqueous solution (polyvinyl alcohol concentration of 0.01 g / mL) under continuous stirring (300 rpm) and nitrogen protection to carry out polymerization reaction at 60°C for 4 h; after the reaction, the polymer product particles were separated and dried at 80°C for 6 h to obtain a spherical macroporous resin (denoted as B3, wherein the pore size distribution range is 4-5 μm);
[0120] The weight ratio of monomer: initiator: dispersant: water (including water in polyvinyl alcohol aqueous solution) is 1:0.08:1:110; the weight ratio of monomer: porogen is 1:1.2; the weight ratio of monomer: cross-linking agent is 1:0.7; the weight ratio of monomer: surfactant is 1:0.35; the weight ratio of monomer: reducing agent is 1:0.25;
[0121] (2) The spherical macroporous resin B3 was immersed in a methanol solution of ethylenediamine (the weight ratio of ethylenediamine to methanol was 1:4), reacted at 60°C for 3 h, and then dried at 80°C for 6 h to obtain a modified resin;
[0122] The weight ratio of spherical macroporous resin B3 to ethylenediamine is 1:40;
[0123] (3) Preparation of template: Ethylenediamine, ethylene glycol diglycidyl ether (modifier) and methanol were thoroughly mixed to obtain a mixture-III. The mixture-III was reacted at 10°C for 48 hours. The reaction product was dried in a vacuum drying oven at 60°C for 24 hours to obtain a liquid template;
[0124] The weight ratio of ethylenediamine to ethylene glycol diglycidyl ether is 1:0.5; the weight ratio of methanol to (ethylenediamine + ethylene glycol diglycidyl ether + methanol) is 110:100;
[0125] Sodium hydroxide, the template, and an aqueous solution containing sodium silicate pentahydrate and sodium metaaluminate (the total concentration of sodium silicate pentahydrate and sodium metaaluminate is 26% by weight) are mixed to obtain a mixed solution-IV; the modified resin is immersed in the mixed solution-IV and reacted at 90° C. for 6 hours. After the reaction, spherical particle products are separated and dried at 120° C. for 24 hours to obtain a spherical core-shell structure composite material (denoted as P3, with an average particle size of 700 μm and a weight ratio of resin shell to molecular sieve core (NaX molecular sieve) in P3 of 100:607);
[0126] The weight ratio of modified resin: sodium hydroxide: template: sodium silicate pentahydrate: sodium aluminate is 100:780:1170:4740:830.
[0127] Example 4
[0128] (1) Monomers (glycidyl methacrylate, cyclohexyl methacrylate and γ-(methacryloyloxy)propyltriethoxysilane, weight ratio of 1:0.8:1.2), trimethylolpropane triacrylate (crosslinker), Span 80 (surfactant), benzoyl peroxide (initiator), toluene (porogen) and N,N-dimethylaniline (reducing agent) were mixed to obtain a mixture-I; the mixture-I was then mixed with water (stirred at 6000 rpm for 10 min) to obtain a mixture-II; the mixture-II was then slowly poured into a polyvinyl alcohol aqueous solution (polyvinyl alcohol concentration of 0.01 g / mL) under continuous stirring (250 rpm) and nitrogen protection to carry out polymerization reaction at 60°C for 3 h; after the reaction, the polymer product particles were separated and dried at 80°C for 6 h to obtain a spherical macroporous resin (denoted as B4, wherein the pore size distribution range is 3-5 μm);
[0129] The weight ratio of monomer: initiator: dispersant: water (including water in polyvinyl alcohol aqueous solution) is 1:0.08:1:112; the weight ratio of monomer: porogen is 1:1.5; the weight ratio of monomer: cross-linking agent is 1:0.8; the weight ratio of monomer: surfactant is 1:0.4; the weight ratio of monomer: reducing agent is 1:0.25;
[0130] (2) impregnating the spherical macroporous resin B4 in the methanol solution of 2-amino-2-methyl-1-propanol (the weight ratio of 2-amino-2-methyl-1-propanol to methanol is 1:4), reacting at 60° C. for 3 h, and then drying at 80° C. for 6 h to obtain a modified resin;
[0131] The weight ratio of spherical macroporous resin B4 to 2-amino-2-methyl-1-propanol is 1:45;
[0132] (3) Preparation of template: 2-amino-2-methyl-1-propanol, 1,2-epoxycyclopentane (modifier) and methanol were fully mixed to obtain a mixture-III. The mixture-III was reacted at 30°C for 36 hours. The reaction product was dried in a vacuum drying oven at 60°C for 24 hours to obtain a liquid template;
[0133] The weight ratio of 2-amino-2-methyl-1-propanol to 1,2-epoxycyclopentane is 1:0.7; the weight ratio of methanol to (2-amino-2-methyl-1-propanol + 1,2-epoxycyclopentane + methanol) is 115:100;
[0134] Sodium hydroxide, the template, and an aqueous solution containing silica sol and sodium metaaluminate (the total concentration of silica sol and sodium metaaluminate is 22 wt%) are mixed to obtain a mixed solution-IV; the modified resin is immersed in the mixed solution-IV and reacted at 80° C. for 12 hours. After the reaction, spherical particle products are separated and dried at 120° C. for 24 hours to obtain a spherical core-shell structure composite material (denoted as P4, with an average particle size of 700 μm and a weight ratio of resin shell to molecular sieve core (NaX molecular sieve) in P4 of 100:566);
[0135] The weight ratio of modified resin: sodium hydroxide: template: silica sol: sodium aluminate is 100:740:740:4120:780.
[0136] Example 5
[0137] (1) Monomers (isodecyl methacrylate, vinyl trimethoxysilane and styrene, weight ratio 1:0.9:1.1), divinylbenzene (crosslinker), Span 80 (surfactant), azobisisobutyronitrile (initiator) and toluene (porogen) were mixed to obtain a mixture-I; the mixture-I was then mixed with water (stirred at 6000 rpm for 10 min) to obtain a mixture-II; the mixture-II was then slowly poured into a polyvinyl alcohol aqueous solution (polyvinyl alcohol concentration of 0.01 g / mL) under continuous stirring (200 rpm) and nitrogen protection to carry out polymerization reaction at 70°C for 24 h; after the reaction, the polymer product particles were separated and dried at 80°C for 6 h to obtain a spherical macroporous resin (denoted as B5, wherein the pore size distribution range is 3-5 μm);
[0138] The weight ratio of monomer: initiator: dispersant: water (including water in polyvinyl alcohol aqueous solution) is 1:0.13:1:110; the weight ratio of monomer: porogen is 1:1.4; the weight ratio of monomer: cross-linking agent is 1:0.7; the weight ratio of monomer: surfactant is 1:0.5;
[0139] (2) The spherical macroporous resin B5 was immersed in a methanol solution of N-(aminoethyl)piperazine (the weight ratio of N-(aminoethyl)piperazine to methanol was 1:4.5), reacted at 55°C for 2.5 hours, and then dried at 80°C for 6 hours to obtain a modified resin;
[0140] The weight ratio of spherical macroporous resin B5 to N-(aminoethyl)piperazine is 1:60;
[0141] (3) Preparation of template: N-(aminoethyl)piperazine, 2,3-epoxy-1-cyclohexanone (modifier) and methanol were fully mixed to obtain a mixture-III. The mixture-III was reacted at 25°C for 36 hours. The reaction product was dried in a vacuum drying oven at 60°C for 24 hours to obtain a liquid template;
[0142] The weight ratio of N-(aminoethyl)piperazine to 2,3-epoxy-1-cyclohexanone is 1:1.5; the weight ratio of methanol to (N-(aminoethyl)piperazine + 2,3-epoxy-1-cyclohexanone + methanol) is 123:100;
[0143] Sodium hydroxide, the template, and an aqueous solution containing water glass and sodium metaaluminate (the total concentration of water glass and sodium metaaluminate is 19 wt%) are mixed to obtain a mixed solution-IV; the modified resin is immersed in the mixed solution-IV and reacted at 90° C. for 6 h. After the reaction, spherical particle products are separated and dried at 120° C. for 24 h to obtain a spherical core-shell structure composite material (denoted as P5, with an average particle size of 800 μm and a weight ratio of resin shell to molecular sieve core (NaX molecular sieve) of 100:496 in P5);
[0144] The weight ratio of modified resin: sodium hydroxide: template: water glass: sodium aluminate is 100:719:725:3890:736.
[0145] Example 6
[0146] (1) Monomers (isopropyl methacrylate, vinyl trimethoxysilane and α-methylstyrene, weight ratio of 1:0.7:1.3), divinylbenzene (crosslinker), Span 80 (surfactant), azobisisobutyronitrile (initiator) and toluene (porogen) were mixed to obtain a mixture-I; the mixture-I was then mixed with water (stirred at 6000 rpm for 10 min) to obtain a mixture-II; the mixture-II was then slowly poured into a polyvinyl alcohol aqueous solution (polyvinyl alcohol concentration of 0.01 g / mL) under continuous stirring (250 rpm) and nitrogen protection to carry out polymerization reaction at 70°C for 24 h; after the reaction, the polymer product particles were separated and dried at 80°C for 6 h to obtain a spherical macroporous resin (denoted as B6, wherein the pore size distribution range is 4-6 μm);
[0147] The weight ratio of monomer: initiator: dispersant: water (including water in polyvinyl alcohol aqueous solution) is 1:0.12:1:110; the weight ratio of monomer: porogen is 1:1.3; the weight ratio of monomer: cross-linking agent is 1:0.7; the weight ratio of monomer: surfactant is 1:0.6;
[0148] (2) The spherical macroporous resin B6 was immersed in a methanol solution of isobutanolamine (the weight ratio of isobutanolamine to methanol was 1:5), reacted at 50°C for 3 h, and then dried at 80°C for 6 h to obtain a modified resin;
[0149] The weight ratio of spherical macroporous resin B6 to isobutanolamine is 1:70;
[0150] (3) Preparation of template: Isobutanolamine, 3-[(2,3)-epoxypropyloxy]propylmethyldimethoxysilane (modifier) and methanol were fully mixed to obtain a mixture-III. The mixture-III was reacted at 30°C for 36 hours. The reaction product was dried in a vacuum drying oven at 60°C for 24 hours to obtain a liquid template;
[0151] The weight ratio of isobutanolamine to 3-[(2,3)-epoxypropyloxy]propylmethyldimethoxysilane is 1:1.9; the weight ratio of methanol to (isobutanolamine + 3-[(2,3)-epoxypropyloxy]propylmethyldimethoxysilane + methanol) is 132:100;
[0152] Sodium hydroxide, the template, and an aqueous solution containing silica sol and sodium metaaluminate (the total concentration of silica sol and sodium metaaluminate is 17 wt%) are mixed to obtain a mixed solution-IV; the modified resin is immersed in the mixed solution-IV and reacted at 80° C. for 6 h. After the reaction, spherical particle products are separated and dried at 120° C. for 24 h to obtain a spherical core-shell structure composite material (denoted as P6, with an average particle size of 850 μm and a weight ratio of resin shell to molecular sieve core (NaX molecular sieve) in P6 of 100:451);
[0153] The weight ratio of modified resin: sodium hydroxide: template: silica sol: sodium aluminate is 100:699:708:3788:619.
[0154] Example 7
[0155] (1) The same method as step (1) of Example 6 was followed to obtain a spherical macroporous resin (denoted as B6);
[0156] (2) The spherical macroporous resin B6 was immersed in a methanol solution of 1-(2-aminoethyl)piperidine (the weight ratio of 1-(2-aminoethyl)piperidine to methanol was 1:5), reacted at 50°C for 3 h, and then dried at 80°C for 6 h to obtain a modified resin;
[0157] The weight ratio of spherical macroporous resin B6 to 1-(2-aminoethyl)piperidine is 1:70;
[0158] (3) Preparation of template: 1-(2-aminoethyl)piperidine, glycidol (modifier), and methanol were thoroughly mixed to obtain a mixture-III, and the mixture was reacted at 30°C for 36 h. The reaction product was dried in a vacuum drying oven at 60°C for 24 h to obtain a liquid template;
[0159] The weight ratio of 1-(2-aminoethyl)piperidine to glycidol is 1:1.9; the weight ratio of methanol to (1-(2-aminoethyl)piperidine + glycidol + methanol) is 132:100;
[0160] Sodium hydroxide, the template, and an aqueous solution containing silica sol and sodium metaaluminate (the total concentration of silica sol and sodium metaaluminate is 17% by weight) are mixed to obtain a mixed solution-IV; the modified resin is immersed in the mixed solution-IV and reacted at 80° C. for 6 hours. After the reaction, spherical particle products are separated and dried at 120° C. for 24 hours to obtain a spherical core-shell structure composite material (denoted as P7, with an average particle size of 840 μm and a weight ratio of resin shell to molecular sieve core (NaX molecular sieve) of 100:446 in P7);
[0161] The weight ratio of modified resin: sodium hydroxide: template: silica sol: sodium aluminate is 100:699:708:3788:619.
[0162] Example 8
[0163] (1) The same method as step (1) of Example 6 was followed to obtain a spherical macroporous resin (denoted as B6);
[0164] (2) impregnating the spherical macroporous resin B6 in the methanol solution of 1-(2-aminoethyl)piperidine (the weight ratio of 1-(2-aminoethyl)piperidine to methanol is 1:5), reacting at 50° C. for 3 h, and then drying at 80° C. for 6 h to obtain a modified resin;
[0165] The weight ratio of spherical macroporous resin B6 to 1-(2-aminoethyl)piperidine is 1:70;
[0166] (3) Preparation of template: piperazine, 3-[(2,3)-epoxypropyloxy]propylmethyldimethoxysilane (modifier) and methanol were fully mixed to obtain a mixture-III, and the mixture was reacted at 30°C for 36 hours. The reaction product was dried in a vacuum drying oven at 60°C for 24 hours to obtain a liquid template;
[0167] The weight ratio of piperazine to 3-[(2,3)-epoxypropyloxy]propylmethyldimethoxysilane is 1:1.9; the weight ratio of methanol to (piperazine + 3-[(2,3)-epoxypropyloxy]propylmethyldimethoxysilane + methanol) is 132:100;
[0168] Sodium hydroxide, the template, and an aqueous solution containing silica sol and sodium metaaluminate (the total concentration of silica sol and sodium metaaluminate is 17 wt%) are mixed to obtain a mixed solution-IV; the modified resin is immersed in the mixed solution-IV and reacted at 80° C. for 6 h. After the reaction, spherical particle products are separated and dried at 120° C. for 24 h to obtain a spherical core-shell structure composite material (denoted as P8, with an average particle size of 845 μm and a weight ratio of resin shell to molecular sieve core (NaX molecular sieve) in P8 of 100:439);
[0169] The weight ratio of modified resin: sodium hydroxide: template: silica sol: sodium aluminate is 100:699:708:3788:619.
[0170] Comparative Example 1
[0171] A core-shell structure composite material (denoted as DP1) was prepared according to the method of steps (2) and (3) disclosed in Example 1 of CN117160429A.
[0172] Comparative Example 2
[0173] The method of Example 8 was followed, except that in step (3), an equal weight of tetrapropylammonium bromide was used as a template, and the other steps and conditions were the same as those of Example 8, to obtain a spherical core-shell structure composite material (denoted as DP2, with an average particle size of 910 μm and a weight ratio of resin shell to molecular sieve core of 100:370 in DP2).
[0174] Comparative Example 3
[0175] The method of Example 8 is followed, except that, in step (3), sodium hydroxide, the template and an aqueous solution containing silica sol (the concentration of silica sol is 9 wt%) are mixed to obtain a mixed solution; the modified resin is immersed in the mixed solution, reacted at 80°C for 3 h, and after the reaction, the spherical particle product is separated and dried at 120°C for 6 h; the dried spherical particle product is then immersed in an aqueous solution containing sodium metaaluminate (the concentration of sodium metaaluminate is 8 wt%), reacted at 80°C for 3 h, and after the reaction, the spherical particle product is separated and dried at 120°C for 24 h to obtain a spherical core-shell structure composite material (denoted as DP3, the average particle size of DP3 is 890 μm, and the weight ratio of resin shell to molecular sieve core in PD3 is 100:388); wherein the weight ratio of modified resin: sodium hydroxide: template: silica sol: sodium metaaluminate is 100:699:708:3788:619. Other steps and conditions are the same as in Example 8.
[0176] Test Case
[0177] 1. Hydrophobic performance test
[0178] The composite materials P1-P8 prepared in Examples 1-8 were tested for water absorption. The test process is as follows:
[0179] Weigh a certain mass of sample and vacuum dry it at 150°C for 12 hours. Place the dried sample on a vapor adsorption instrument for water absorption test (40°C, relative humidity 20% RH). Calculate the water absorption according to the following formula:
[0180]
[0181] The results are shown in Table 1.
[0182] Table 1
[0183] Composite materials Water absorption at 40℃, 20%RH / weight% P1 11.0 P2 12.6 P3 14.1 P4 15.7 P5 17.2 P6 19.1 P7 20.2 P8 21.6 NaX molecular sieve 29.1
[0184] Note: The chemical composition of the NaX molecular sieve in Table 1 is the same as that of the molecular sieve core in P1.
[0185] As shown in Table 1, the core-shell composite materials P1-P8 prepared by the present invention exhibit excellent hydrophobic properties, absorbing no more than 22% by weight at 40°C and 20% relative humidity. Compared to NaX molecular sieve, composite material P1 exhibits significantly lower water absorption, demonstrating the strong hydrophobic barrier effect of its resin shell.
[0186] 2. CO2 adsorption performance test
[0187] The composite materials P1-P8 and DP1-DP3 prepared in Examples 1-8 and Comparative Examples 1-3 were tested for CO2 adsorption performance, and the process was as follows:
[0188] A certain mass of sample was placed under vacuum heating at 120°C for 3 hours. The dried sample was placed in a gravimetric adsorption analyzer and the CO2 adsorption capacity of the sample was tested by passing a mixed gas of 10% by volume CO2 and 20% by volume water vapor (the remaining components were balanced by nitrogen) at 40°C. The sample was then desorbed in a CO2 atmosphere at 120°C. The amount of desorbed CO2 was the CO2 working adsorption capacity of the sample. The results are shown in Table 2.
[0189] Table 2
[0190] Composite materials <![CDATA[CO2 working adsorption capacity / mmol / g]]> P1 0.94 P2 0.91 P3 0.89 P4 0.86 P5 0.84 P6 0.80 P7 0.76 P8 0.73 DP1 0.38 DP2 0.41 DP3 0.26 NaX molecular sieve 0.49
[0191] Note: The chemical composition of the NaX molecular sieve in Table 2 is the same as that of the molecular sieve core in P1.
[0192] As shown in Table 2, the core-shell composite materials P1-P8 prepared by the preparation method of the present invention exhibited CO2 working adsorption capacities of no less than 0.7 mmol / g under flue gas adsorption conditions of 10 vol% CO2 at 40°C and regeneration conditions of 100 vol% CO2 at 120°C, significantly exceeding those of DP1-DP3. Comparison of the CO2 working adsorption capacity of composite material P1 with that of NaX molecular sieves demonstrates that hydrophobic modification using the present method does not degrade the adsorbent's CO2 adsorption performance, maintaining excellent CO2 working adsorption capacity and surpassing that of the corresponding NaX molecular sieve.
[0193] 3. CO2 / N2 adsorption selectivity test
[0194] The composite materials P1-P8 and DP1-DP3 prepared in Examples 1-8 and Comparative Examples 1-3 were subjected to a CO2 / N2 adsorption selectivity test, and the process was as follows:
[0195] A certain mass of sample was heated in vacuum at 120°C for 3 h. The dried sample was placed in a static volumetric adsorption analyzer, and gases containing CO2 and N2 (containing 10 vol% CO2 and 70 vol% N2) were introduced at 40°C. The CO2 / N2 adsorption selectivity of the sample was calculated according to the ideal solution adsorption theory (IAST). The results are shown in Table 3.
[0196] Table 3
[0197] Composite materials <![CDATA[CO2 / N2 adsorption selectivity]]> P1 262 P2 259 P3 255 P4 239 P5 233 P6 229 P7 213 P8 201 DP1 180 DP2 185 DP3 177 NaX molecular sieve 187
[0198] Note: The chemical composition of the NaX molecular sieve in Table 3 is the same as that of the molecular sieve core in P1.
[0199] It can be seen from the data in Table 3 that the core-shell structure composite materials P1-P8 prepared by the preparation method of the present invention have a CO2 / N2 adsorption selectivity of not less than 200 at 40°C and 10% by volume of CO2 and 70% by volume of N2. The selectivity of CO2 adsorption is significantly higher than that of DP1-DP3 and NaX molecular sieve, showing excellent CO2 / N2 selectivity.
[0200] The preferred embodiments of the present invention have been described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, various simple variations of the technical solution of the present invention may be made, including combining the various technical features in any other appropriate manner. These simple variations and combinations should also be regarded as disclosed in the present invention and fall within the scope of protection of the present invention.
Claims
1. A method for preparing a core-shell structure composite material, characterized in that: The preparation method comprises: (1) in the presence of an initiator and a dispersant, a reaction system containing a monomer, a porogen, and water is subjected to a first reaction to obtain a spherical macroporous resin; (2) subjecting the spherical macroporous resin to a second reaction with a first organic amine to obtain a modified resin; (3) subjecting the modified resin to a third reaction with a solution containing an alkali, a template, a silicon source, and an aluminum source to obtain a core-shell structure composite material; Wherein, the monomer is selected from at least one of an acrylate monomer, an alkenylbenzene and a silane coupling agent containing an unsaturated bond; The template is prepared by a fourth reaction of raw materials containing a second organic amine and a modifier; wherein the modifier is selected from at least one of chloroalkanes, epoxy-containing acrylates, epoxy-containing alkanes, epoxy-containing alcohols, epoxy-containing ketones, and epoxy-containing silane coupling agents.
2. The preparation method according to claim 1, wherein In step (1), the monomer is selected from acrylate monomers and / or silane coupling agents containing unsaturated bonds.
3. The preparation method according to claim 1 or 2, wherein The acrylic acid ester monomer is selected from at least one of isodecyl methacrylate, phenyl methacrylate, glycidyl methacrylate, isopropyl methacrylate, ethyl methacrylate, cyclohexyl methacrylate, dodecafluoroheptanoate methacrylate and pentafluorophenyl methacrylate; and / or, the alkenylbenzene is at least one selected from styrene, 3-chlorostyrene and α-methylstyrene; And / or, the silane coupling agent containing an unsaturated bond is at least one selected from γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane and γ-(methacryloxy)propyltriethoxysilane; And / or, the porogen is selected from at least one of toluene, xylene and cyclohexane.
4. The preparation method according to claim 1 or 2, wherein In step (1), the weight ratio of the monomer:initiator:dispersant:water is 1:(0.005-0.2):(0.5-1):(110-118); And / or, the weight ratio of the monomer:porogen is 1:(0.8-2).
5. The preparation method according to claim 1 or 2, wherein In step (1), the reaction system further comprises a cross-linking agent, a surfactant and an optional reducing agent.
6. The preparation method according to claim 5, wherein The weight ratio of the monomer to the cross-linking agent is 1:(0.5-2); and / or, the weight ratio of the monomer:surfactant is 1:(0.2-0.5); And / or, the weight ratio of the monomer:reducing agent is 1:(0.25-0.8).
7. The preparation method according to claim 1 or 2, wherein In step (1), the conditions of the first reaction include: reacting under stirring and protective atmosphere, the reaction temperature is 50-90° C., the reaction time is 0.1-24 h, and the stirring rate is 150-350 rpm.
8. The preparation method according to claim 1 or 2, wherein In step (2), the first organic amine is selected from at least one of ethanolamine, triethanolamine, ethylenediamine, trimethylamine, isobutanolamine, polyethyleneimine, piperazine, N-(aminoethyl)piperazine, 2-aminomethylpiperidine, 1-(2-aminoethyl)piperidine and 2-amino-2-methyl-1-propanol; and / or, the weight ratio of the spherical macroporous resin to the first organic amine is 1:(10-90); And / or, the conditions of the second reaction include: reaction temperature of 50-80° C., reaction time of 0.5-3 h.
9. The preparation method according to claim 1 or 2, wherein In step (3), the silicon source is selected from at least one of silica sol, water glass, sodium silicate and sodium aluminum silicate; And / or, the aluminum source is sodium metaaluminate and / or aluminum sulfate.
10. The preparation method according to claim 1 or 2, wherein In step (3), the weight ratio of the modified resin: base: template: silicon source: aluminum source is 100: (195-1560): (390-1660): (1360-6162): (315-1560); And / or, the conditions of the third reaction include: reaction temperature of 60-120° C., reaction time of 6-24 h.
11. The preparation method according to claim 1 or 2, wherein The second organic amine is selected from at least one of ethanolamine, triethanolamine, ethylenediamine, trimethylamine, isobutanolamine, polyethyleneimine, piperazine, N-(aminoethyl)piperazine, 2-aminomethylpiperidine, 1-(2-aminoethyl)piperidine and 2-amino-2-methyl-1-propanol; and / or, the modifier is selected from at least one of ethylene glycol diglycidyl ether, epichlorohydrin, glycidol, 1,2-epoxycyclopentane, 2,3-epoxy-1-cyclohexanone, 3-[(2,3)-epoxypropyloxy]propylmethyldimethoxysilane and γ-glycidyloxypropyltrimethoxysilane; And / or, the weight ratio of the second organic amine to the modifier is 1:(0.5-3).
12. The preparation method according to claim 11, wherein The conditions of the fourth reaction include: reaction temperature of 10-60° C., and reaction time of 12-48 h.
13. A core-shell structure composite material prepared by the preparation method according to any one of claims 1 to 12.
14. The core-shell structure composite material according to claim 13, wherein: The core-shell structure composite material comprises: a resin shell, and a molecular sieve core wrapped in the resin shell; wherein the weight ratio of the resin shell to the molecular sieve core is 100:(300-800); and / or, the average particle size of the core-shell structure composite material is 500-1000 μm; And / or, the core-shell structure composite material has a water absorption capacity of ≤22 wt % at 40° C. and a relative humidity of 20% RH.
15. Use of the core-shell structure composite material according to claim 13 or 14 as a carbon dioxide adsorbent in the purification of flue gas containing carbon dioxide.
16. The use according to claim 15, wherein: The water content in the flue gas containing carbon dioxide is 10-50% by volume.
Citation Information
Patent Citations
Preparation and application of non-ionic macroporous resin microspheres
CN106589210A
Molecular sieve and porous organic polymer core-shell structure composite adsorbent and preparation method thereof
CN113198433A
Hydrophobic CO2 adsorbent with core-shell structure as well as preparation method and application thereof
CN117160429A